Largo Caballero (note) - A. C.
Mr Tewson LARGO CABALLERO. In conversation with Stolz, the latter asked whether it would be possible for us to wire Sir Walter and secure the intervention of the A.F. of L. to obtain Caballero's release, possibly by means of U.S. visa I dont know if you think we might do something for the others, particularly Pascual Tomas, on the same lines. Please approve or otherwise the following text. "Caballero (and Pascual Tomas?) handed over by Vichy to Spanish Government. Please enlist support Green and others. Have approached Halifax. Tewson". A.C. 292/946/13/52(i)